(untitled) (Tạp chí Y học Cộng đồng, 2026)
Undernutrition and obesity are prevalent nutritional issues among adolescents. This cross-sectional study aimed to evaluate the nutritional status and associated factors among secondary school students in Chu Se district, Gia Lai province. Participants were selected using a stratified random sampling method. Data collection included using a structured questionnaire based on the Global School-based Student Health Survey and Physical Activity Ǫuestionnaire for Older Children questionnaire, and students’ height and weight were measured directly using a tape measure and a digital scale. Undernutrition and obesity were determined using the WHO AnthroPlus software. Multivariable logistic regression analysis was employed to explore associations, with statistical significance set at p<.05. A total of 404 students were included in the study, with the prevalence of stunting, wasting, and overweight/obesity being 2.9%, 8.6%, and 19.6%, respectively. Gender (p<.001), age, and sleep duration were significantly associated with overweight/obesity (p<.05). Although the rate of stunting among students is low, the prevalence of wasting and overweight/obesity is significantly high. These findings highlight the importance of promoting school-based and family-centered interventions to improve students’ nutritional status.